Quality of life assessments in clinical practice using either the EORTC-QLQ-C30 or the SEIOQL-DW: a randomized study - Åsa Kettis; Hanna Fagerlind; Jan-Erik Frödin; Bengt Glimelius; Lena Ring (SpringerOpen, 2021)
Abstract Background Effective patient-physician communication can improve patient understanding, agreement on treatment and adherence. This may, in turn, impact on clinical outcomes and patient quality of life (QoL). One way to improve communication is by using patient-reported outcome measures (PROMs). Heretofore, studies of the impact of using PROMs in clinical practice have mostly evaluated the use of standardized PROMs. However, there is reason to believe that individualized instruments may be more appropriate for this purpose. The aim of this study is to compare the effectiveness of the standardized QoL-instrument, the European Organization for Research and Treatment of Cancer Quality of Life C-30 (EORTC-QOL-C30) and the individualized QoL instrument, the Schedule for the Evaluation of Individual Quality of Life-Direct Weighting (SEIQoL-DW), in clinical practice. Methods In a prospective, open-label, controlled intervention study at two hospital out-patient clinics, 390 patients with gastrointestinal cancer were randomly assigned either to complete the EORTC-QOL-C30 or the SEIQoL-DW immediately before the consultation, with their responses being shared with their physician. This was repeated in 3-5 consultations over a period of 4-6 months. The primary outcome measure was patients' health-related QoL, as measured by FACIT-G. Patients' satisfaction with the consultation and survival were secondary outcomes. Results There was no significant difference between the groups with regard to study outcomes. Neither intervention instrument resulted in any significant changes in health-related QoL, or in any of the secondary outcomes, over time. This may reflect either a genuine lack of effect or sub-optimization of the intervention. Since there was no comparison to standard care an effect in terms of lack of deterioration over time cannot be excluded. Conclusions Future studies should focus on the implementation process, including the training of physicians to use the instruments and their motivation for doing so. The effects of situational use of standardized or individualized instruments should also be explored. The effectiveness of the different approaches may depend on contextual factors including physician and patient preferences.